RADICAL APPROACH OF WRITEN TEXTS FROM COLLECTIVE AUTHORS (Fiep Bulletin - online, 2020)
Questions referring to preserve nature are relevant, as well as studies about textual production in the universities. This paper produces critical analysis of discourses present in 16 letters written by university students on physical education, about principles of Earth Letter.  Theoretical support is based on discourse analysis, in the thread of Norman Fairclough and Sebastião Votre, and from content analysis, following the ideas of Laurence Bardin. In final considerations, we indicate that the proposal of pedagogical recontextualization involves students in the Project of writing and that, once motivated, these students produce more convinced texts.